MANAJEMEN PENDIDIKAN KARAKTER SOSIAL DALAM KEGIATAN KARANG TARUNA PADA LOMBA DUTA PELAJAR KARANG TARUNA KABUPATEN KARAWANG TAHUN 2025 - Sudirman, Dhani; Sukma Firmansyah, Very (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The management of social character education in non-formal education plays a strategic role in shaping students’ social attitudes, leadership, and civic participation. This study aims to analyze the implementation of social character education management in the Duta Pelajar Competition organized by Karang Taruna of Karawang Regency in 2025. This research employed a qualitative approach using a case study method. The research subjects consisted of 100 student participants from senior high schools (SMA/SMK/MA/SLB) and Karang Taruna administrators. Data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that social character education was managed systematically through the functions of planning, organizing, actuating, and controlling (POAC). The social character values developed include social care, responsibility, cooperation, tolerance, leadership, social communication, and inclusivity. These findings confirm that youth activities managed through an educational management approach are effective in strengthening students’ social character and are relevant to Karang Taruna policies as regulated by the Ministry of Social Affairs.